SURGICAL TECHNIQUES USED IN LINGUAL FRENOTOMIES: LITERATURE REVIEW - Caroline Ribeiro Lacerda, Anne; Jordhan da Silva Sá, Cauã; Freitas de Sá, Fernanda; Alves Freitas Cruz, Kádja; Gama de Oliveira Muniz, Letícia; Jordania Lino Figueredo, Lívia; Karinelly da Silva Fonseca, Louise; de Souza Pereira, Malvina (Health and Society, 2025)
Introduction: The study aims to highlight the indications, advantages, disadvantages, and technological advances related to the procedure. Objective: This article reviews the main surgical techniques used in lingual frenotomy to treat ankyloglossia, also known as “tongue-tie,” which affects oral function and can cause difficulties in breastfeeding and speech. Methodology: The research was carried out by selecting relevant scientific articles, dissertations, and theses from the National Center for Biotechnology Information (PubMed), Virtual Health Library (BVS), and Scientific Electronic Library Online (SciELO) databases, in English, Spanish, and Portuguese. Studies published between 2012 and 2024 were included. Discussion: Ankyloglossia, or “tongue-tie,” results from the incomplete formation of the lingual frenulum, affecting speech, breathing, and breastfeeding. Early diagnosis is crucial, with the Tongue Test being mandatory in Brazil since 2014. Treatment can be conservative or surgical, such as frenotomy, with laser standing out for its precision and rapid recovery. Imaging technologies help in surgical planning, increasing the safety and efficacy of the procedure. The joint action of speech therapists, pediatricians and dentists is essential. Results: The literature review includes articles selected based on previously defined inclusion and exclusion criteria. Searches were performed in the PubMed, BVS and SciELO databases, covering publications in English, Spanish and Portuguese. Conclusion: We conclude that it is essential to understand the different techniques and their implications, choosing the most appropriate method based on the patient’s needs. With the continuous evolution of technologies, we understand that there are few studies in the literature and it is expected that lingual frenotomy will become increasingly effective, improving the quality of life of individuals with ankyloglossia.